The role of networking competencies in social enterprise performance - Aija Sannikova; Jelena Titko; Janis Kudins (Business, Management and Economics Engineering)
Purpose – The goal of this research was to identify the need for networking competencies in social enterprises rated by the managerial personnel of social enterprises and academic staff of universities in Latvia.